Legume establishment on native pastures of cerrados - Couto, Walter; Gomes, Darci T.; Leite, Gilberto G.; Silva, José Carlos S. (Pesquisa Agropecuaria Brasileira, 2014)
Several methods for introducing legumes into a native pasture were tested in an open grass savanna with some shrubs and small trees, which is known as "campo sujo", in the Cerrados region of Brazil. Three legumes (Calopogonium mucunoides (Desv.), Stylosanthes capitata (Vog.) and Galactia striata (Jacq.)) were tested with all planting methods. Planting methods consisted of oversowing, oversowing after disc-harrowing, and sodseeding. Each method was tested with and without previous burning. Results showed that all planting methods which provided some soil surface disturbance were more effective than oversowing in terms of number of plants established. Stylosanthes capitata was slow to establish but contributed more to total dry matter production during the second year than the other species. The highest dry matter production and crude protein content were obtained in the native pasture + Stylosanthes capitata treatment. Dry matter yield as high as 2,266 kg/ha and 6.4% crude protein content were recorded. In the unimproved native pasture (control) the dry matter and crude protein levels obtained were 738 kg/ha-1 and 2.4%, respectively.